Clamp cell with in situ pressure monitoring for low-temperature neutron scattering measurements. Issue 4 (2nd October 2018) - Podlesnyak, A.; Loguillo, M.; Rucker, G. M.; Haberl, B.; Boehler, R.; Ehlers, G.; Daemen, L. L.; Armitage, D.; Frontzek, M. D.; Lumsden, M.
ABSTRACT: A clamp pressure cell for neutron scattering experiments at low temperatures and in external magnetic fields under pressure up to 2 GPa has been fabricated and tested. The cell provides optical access to the sample space that allows instantaneous pressure determination during sample loading, cooling and measuring using ruby and/or samarium doped strontium tetraborate fluorescence monitoring. A new calibration curve of the pressure-induced shift of the 7 D 0 − 5 F 0 (0-0) line in the fluorescent spectrum of SrB 4 O 7 :Sm 2 + for moderate pressures, P ≤ 2  GPa, is given.